Ecological monitoring in the region of Akademik Vernadsky Antarctic station - Bondar, S.B.; Orlova, I.G.; Popov, Yu.I.; Ukrainsky, V.V.; Usenko, V.P. (Український антарктичний журнал, 2003)
The issues of organization and carrying out of ecological monitoring in the region of the Ukrainian Antarctic Station “Akademik Vernadsky” are taken up in the report. The information about the basic circulation flows, temporal (daily and annual) and spatial changeability of hydrological & hydrochemical ingredients as well as the vertical hydrological & hydrochemical water structure are presented on the basis of 1997-1998 experimental data. The description of the modern state of the chemical pollution of the basic elements of the Argentina Archipelago Islands` shallow water ecosystem. The broad spectrum of pollutants, such as different components of oil pollution, including carcinogenic polyaromatic hydrocarbons, highly toxic chlorinated hydrocarbons, heavy metals have been found in the majority of the ecosystem`s elements under analysis. The local areas of oil pollution have been found in the region of Galindez Isles. The obtained results are the part of the experimental data base for solving fundamental and applied problems including the problem of environmental protection. It is necessary to continue such investigations for studying the tendencies, for forecasting the vulnerable Antarctic ecosystems` state and for working up measures to protect ecosystems from the further pollution. У доповіді розглянуті питання організації і виконання екологічного моніторингу в районі української антарктичної станції Академік Вернадський. На основі експериментальних даних 1997-1998 рр. представлені дані про основні циркуляційні потоки, тимчасову (добову, міжрічну) і просторову мінливість гідролого-гідрохімічних інгредієнтів, вертикальну гідролого-гідрохімічну структуру вод. Наведено характеристику сучасного стану хімічного забруднення основних елементів екосистеми шхерного мілководдя. У більшості аналізованих елементів екосистеми виявлений широкий спектр забруднюючих речовин: різні компоненти нафтового забруднення, включаючи канцерогенні поліароматичні вуглеводні, високотоксичні хлоровані вуглеводні, важкі метали. Виявлено локальні ділянки нафтового забруднення в районі острова Галіндез. Отримані результати є частиною експериментальної бази даних для рішення фундаментальних і прикладних, у тому числі природоохоронних задач. Продовження цих досліджень необхідно для вивчення тенденцій, прогнозування стану уразливих антарктичних екосистем і розробки заходів щодо запобігання їхнього подальшого забруднення.